INSEMINASI BUATAN DALAM KAJIAN DAN ATURAN HUKUM ISLAM - Irmawati Carolina (Universitas Bina Sarana Informatika, 2011)
Artificial insemination as the development of science and technology, including the development ofthe human mind to be thankful for and utilized for the improvement of human living standards to ahigher level and more terhormat.Hasil human thought with religion will be balanced if the ideasare based on a system and method of thinking is correct, and excavated by the power of religion isalso true ijtihad. Both are strong mutual-menguatkan. Klonasi terms of broadening its theologicalaspects of the introduction of Iradat Divine nature, even as evidence of sophistication klonasiSunna of God contained in His creation and to prove to his Almighty power.Artificial insemination with sperm cell and ovum of the husband and wife own and not transferredthe embryo into the womb of another woman (surrogate mothers) are allowed to Islam, if at allrelevant conditions of husband and wife who really need it. And the status of the child of this kindinsemination legitimate under Islam.Keywords: Artificial Insemination, Study of Islamic Law